Broccoli and cauliflower seedling emergence and production in different substrates - Fiorin, Tatiana Tasquetto; Menegaes, Janine Farias; Rodrigues, Andrielle Magrini; Swarowsky, Alexandre (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
Inflorescence brassicas, such as broccoli and cauliflower, rich in fiber and vitamins, are widely consumed in Brazil, and present an average production of 23 t ha-1. Despite this demand, the quality of seedlings of both species is one of the main factors that limit production. Thus, the objective of this study was to evaluate broccoli and cauliflower seedling emergence and production in different substrates, using the irrigation method named Deep Film Technique (DFT) on a table. The experiment was carried out in a completely randomized design, 7×2: substrate compositions (volumetric proportions of 1:0:0; 0:1:0; 0:0:1; 1:1:1; 1:1:0; 1:0:1 and 0:1:1, containing commercial substrate Carolina Soil®, carbonized rice husk and medium textured sand) and inflorescence brassicas (broccoli and cauliflower), with four replications. Each experimental unit consisted of 50 seeds/seedlings. At 21 days after sowing (DAS), it was evaluated the percentage, index, time, speed and frequency of emergence, and, at 35 DAS, clod stability, number of leaves and seedling length. It was observed that there was good seed germination and seedling formation for both species in all substrate compositions and with the aid of the DFT irrigation method on a table. Under these conditions, for both species, substrate compositions of 1:0:0; 1:1:1 and 1:1:0 are recommended.